Mapping Meta-Therapy in Voice Interventions onto the Rehabilitation Treatment Specification System - Helou, Leah B.; Gartner-Schmidt, Jackie L.; Hapner, Edie R.; Schneider, Sarah L.; Van Stan, Jarrad H. (Seminars in Speech and Language, 2021)
Meta-therapy refers to the clinical dialogue via which direct and indirect voice treatments are introduced and discussed, and which helps build a useful conceptual framework for voice therapy. Meta-therapy was idiosyncratically defined in previous work. However, the current colloquial narrative of meta-therapy is not standardized or specific enough to be reliably taught, rigorously studied, or clinically delivered with high fidelity. Therefore, this article uses a standard framework (the Rehabilitation Treatment Specification System or RTSS) to further articulate and operationalize meta-therapy in vocal rehabilitation. Meta-therapy's conceptual framework generally aligns with the RTSS's treatment theory and associated concepts; e.g., the treatment component and its underlying ingredients, mechanisms of action, and target. Because the treatment theories in meta-therapy most frequently involve mechanisms of action related to information processing, they primarily map onto the RTSS's Representations treatment components. The treatment targets in meta-therapy are often focused on changes in the patient's cognitions, knowledge, beliefs, attitudes, intentions, and/or awareness regarding voice-related modifications. The ingredients in meta-therapy are frequently clinician actions conveying information with the goal of appropriately shaping the patient's mental representations, and are delivered with verbal cues, stories, analogies, etc. This manuscript provides specific examples of how meta-therapy is applied in clinical voice practice. Considerations for future investigation of meta-therapy are proposed.
Keywords: meta-therapy; Rehabilitation Treatment Specification System; voice therapy; treatment theory; expectations